A Comparative Study for Electricity Generation and Wastewater Treatment from Palm Oil Mill Effluent by Microbial Fuel Cell using Different Sizes of Electrodes - Kumar, Ravinder; Singh, Lakhveer; Zularisam, A. W. (Penerbit Universiti Malaysia Pahang, 2014)
The growth in the worldwide of energy demand every year and the over consumption of non renewable sources of energy has led to the identification and use of renewable and cost effective sources of energy. In this context, palm oil mill effluent, which contains high levels of degradable organic materials, has gained importance as a source of electricity generation using a microbial fuel cells (MFC). Two microbial fuel cells were produced, one made up of larger electrodes and the second of comparatively smaller electrodes; for the generation of electricity and wastewater treatment using palm oil mill effluent (POME). A comparative study showed that MFC with larger electrodes had greater efficiency for electricity production, resulted maximum 0.721 V and wastewater treatment, and resulted maximum chemical oxygen demand (COD) removal of 81%, biochemkal,oxygen demand (BOD) removal of 72 % and total organic carbon (TOC) of 82%. On the other hand, MFC with smaller electrodes showed less effective results compared to the fomer MFC.